Tobacco and the Malays: ethnicity, health and the political economy of tobacco in Malaysia. Issue 2 (4th March 2017) - Barraclough, Simon; Morrow, Martha
ABSTRACT: Objectives: To identify the historical nexus between Malaysia's largest and politically dominant ethnic group and the political economy of tobacco, and to consider the implications of this connection for tobacco control. Design: Primary and secondary documentary sources in both English and Malay were analysed to illuminate key events and decisions, and the discourse of industry and government. Sources included: speeches by Malaysian political and industry actors; tobacco industry reports, press releases and websites; government documents; World Health Organization (WHO) tobacco control literature; and press reports. Results: Malays have the highest smoking prevalence among Malaysia's major ethnic groups. The tobacco industry has consistently been promoted as furthering Malay economic development. Malays play the major role in growing and curing. Government-owned Malay development trusts have been prominent investors in tobacco corporations, which have cultivated linkages with the Malay elite. The religious element of Malay ethnicity has also been significant. All Malays are Muslim, and the National Fatwa Council has declared smoking to be haram (forbidden); however, the Government has declined to implement this ruling. Conclusion: Exaggerated claims for the socio-economic benefits of tobacco production, government investment and close links between tobacco corporations and sections of the Malay elite have created a conflict of interest in public policy, limited the focus on tobacco as a health policy issue among Malays and retarded tobacco control policy. More recently, ratification of the WHO Framework Convention on Tobacco Control, regional free trade policies reducing the numbers of growers, concerns about smoking from an Islamic viewpoint, and anxieties about the effects of smoking upon youth have increasingly challenged the dominant discourse that tobacco furthers Malay interests. Nevertheless, the industry remains a formidable political and economic presence in Malaysia that is likely to continue to proclaim that its activities coincide with Malay socio-economic interests.